Proinflammatory Mediators of Toxic Shock and Their Correlation to Lethality - Teresa Krakauer; Marilyn J. Buckley; Diana Fisher (Hindawi Limited, 2010)
Bacterial exotoxins and endotoxins both stimulate proinflammatory mediators but the contribution of each individual toxin in the release of mediators causing lethal shock is incompletely understood. This study examines the cytokine response and lethality of mice exposed to varying doses of staphylococcal enterotoxin B (SEB) or lipopolysaccharide (LPS) and their combinations. In vivo, SEB alone induced moderate levels of IL-2 and MCP-1 and all mice survived even with a high dose of SEB (100 μg/mouse). LPS (80 μg/mouse) caused 48% lethality and induced high levels of IL-6 and MCP-1. SEB induced low levels of TNFα, IL-1, IFNγ, MIP-2, and LPS synergized with SEB in the expression of these cytokines and that of IL-6 and MCP-1. Importantly, the synergistic action of SEB and LPS resulted in lethal shock and hypothermia. ANOVA of cytokine levels by survival status of SEB-plus-LPS groups revealed significantly higher levels of TNFα, IL-6, MIP-2, and MCP-1 in nonsurvivors measured at 8 hours. Significantly higher levels of IFNγ and IL-2 were observed at 21 hours in nonsurvivors of toxic shock compared to those in survivors. Overall, synergistic action of SEB and LPS resulted in higher and prolonged levels of these key cytokines leading to toxic shock.